Analyzing Students’ Critical Thinking Skills in SWOT-Based Problem-Solving - Deni Kadarsah; Risbon Sianturi (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
This study aims to analyze students’ critical thinking skills in SWOT-based problem-solving within the context of the Educational Administration Study Program at Universitas Pendidikan Indonesia. Using a qualitative descriptive design, this study involved ten students who had completed more than six semesters of study. Data were collected through a problem-based task related to educational management and policy, in which participants were asked to identify strengths, weaknesses, opportunities, and threats, and then propose possible solutions. The data were analyzed using NVivo 12 with reference to Costa’s (1985) critical thinking indicators: Elementary Clarification, Basic Support, Inference, Advance Clarification, and Strategies and Tactics. The findings show that in the self-assessment stage, two participants were categorized under Basic Support, six under Inference, and two under Advance Clarification. In the SWOT-based problem-solving task, all participants demonstrated Elementary Clarification, Basic Support, and Inference, indicating their ability to identify problems, support arguments, and draw logical conclusions. However, only two participants reached Advance Clarification and Strategies and Tactics, suggesting that students’ critical thinking remained largely procedural, namely focused on completing analytical steps rather than consistently questioning assumptions, evaluating alternatives, and formulating strategic actions. The study contributes to the application of Costa’s critical thinking framework in Educational Administration learning and shows that SWOT-based tasks can serve as diagnostic tools for identifying students’ reasoning patterns. The findings imply that learning activities should integrate TOWS-based strategy formulation, reflective memos, case-based discussion, and reasoning-oriented assessment rubrics to strengthen students’ reflective and strategic critical thinking.